The role of internal marketing in - Nicolaus, Ingrid (My University, 2011)
The purpose of this research was to investigate the role and responsibilities in the implementation of internal marketing in engineering organisations operating within the mining sector. The literature review revealed that earlier literature attempted to define the term internal marketing, while later literature focussed on various aspects of internal marketing, such, as what constitutes internal marketing; who is responsible for it; and how internal marketing is implemented in an organisation. Drawing from the literature on internal marketing, this report attempts to critically analyse the role of internal marketing in engineering organisations within the mining sector. The report further examines who is responsible for internal marketing and which external-marketing activities are applied internally. A total of 16 in-depth interviews were conducted with management and engineers to assess their understanding of internal marketing. The data was analysed using concept mapping to identity the key themes. A total of 16 in-depth interviews were conducted with managers and engineers of engineering organisations to assess their understanding of internal marketing. The data from the interviews was analysed using concept mapping in order to identity the key themes. The interviews reflected that, despite some confusion as to the understanding of the concept of internal marketing; externalmarketing like activities were being implemented internally. The research further highlighted that the responsibility for internal marketing was found to lie primarily with management, rather than with the marketing department. It is clear that many organisations are unaware that internal marketing practices are being implemented. It would be beneficial to the organisation for these practices to be formalised and co-ordinated through a central point
MBA - WBS
Keywords: Marketing, Internal; Internal marketing; Engineering firms